Moonhead and the music machine - Rae, Andrew (2014)
Meet Joey Moonhead. A normal kid in every way. Except one: he has a moon for a head. Equipped with little else but a boundless imagination and an insatiable desire to be the best musician in existence, Joey Moonhead embarks on a stellar mission to create a machine that is out of this world.
Keywords: Imagination -- Comic books, strips, etc; High school students -- Comic books, strips, etc; Musicians -- Comic books, strips, etc; Graphic novels